Comprehensive analysis of MAPK gene family in Populus trichocarpa and physiological characterization of PtMAPK3‐1 in response to MeJA induction. Issue 1 (10th February 2023) - Wu, Jing; Liang, Xiaoyu; Lin, Miao; Lan, Yangang; Xiang, Yan; Yan, Hanwei
Abstract: Mitogen‐activated protein kinases (MAPKs) play important roles in plant growth and development, as well as hormone and stress responses by signaling to eukaryotic cells, through MAPK cascade, the presence of various cues; thereby, regulating various responses. The MAPK cascade consists mainly of three gene families, MAPK, MAPKK, and MAPKKK, which activate downstream signaling pathways through sequential phosphorylation. Although the MAPK cascade gene family has been reported in several species, there is a lack of comprehensive analysis in poplar. We identified 21 MAPK genes, 11 MAPKK genes, and 104 MAPKKK genes in Populus trichocarpa . The phylogenetic classification was supported by conservative motif, gene structure and motif analysis. Whole genome duplication has an important role in the expansion of MAPK cascade genes. Analysis of promoter cis ‐elements and expression profiles indicates that MAPK cascade genes have important roles in plant growth and development, abiotic and biotic stresses, and phytohormone response. Expression profiling revealed a significant upregulation of PtMAPK3‐1 expression in response to drought, salt and disease stresses. Poplar transiently overexpressing PtMAPK3‐1 and treated with methyl jasmonic acid (MeJA) had higher catalase and peroxidase levels than non‐overexpressing poplar. This work represents the first complete inventory of the MAPK cascade in P. trichocarpa, which reveals that PtMAPK3‐1 is induced by the MeJA hormone and participates in the MeJA‐induced enhancement of the antioxidant enzyme system.